Cuidados paliativos: perfil e percepção do cuidador principal acerca da alimentação - Ana Fernanda Rodrigues Cardoso (2016)
Objectives: Characterize the profile of patients in palliative care at risk for dysphagia and their caregivers and to analyze the perception of the primary caregiver concerning the feeding of patients under their care. Methods: The study was conducted in two stages: integrative literature review and execution of field research. The integrative literature review was performed in the databases LILACS, IBECS, Medline and SciELO. The researched publication period was from 2005 to 2014, in English, Spanish and Portuguese, using the following descriptors: "palliative care", "hospice care," "swallowing" and "swallowing disorders." For the search, boolean operators AND and OR were used. As for the field research, an analytical observational cross-sectional study was conducted in two public hospitals in the city of Belo Horizonte, Minas Gerais. The sample consisted of 30 primary caregivers of hospitalized patients in palliative care at risk for dysphagia. The risk was definedaccording to the Northwestern Dysphagia Patient Check Sheet protocol. The information was collected from medical records and with the participants through semi-structured questionnaire composed of open and closed questions and presenting four topics: patient information, information about the caregiver, perception of the caregivers about feeding and expectations of the caregivers on patients mainway of feeding. Descriptive analysis of frequency distribution of all categorical variables was carried out and analysis of numerical synthesis of continuous variables. To evaluate the characteristics associated with the main feeding route, the chi square test was used. Analyses were performed using the STATA software, version 12.0, considering 5% of significance. Results: The results and discussion were presentedin article format, they are: Article 1 - Palliative Care and Oropharyngeal Dysphagia: integrative literature review; Article 2 - Profile of patients at risk for dysphagia in hospitalized palliative care and their primary caregivers; Article 3 - Palliative Care: perception of the primary caregiver about the feeding of hospitalized patients. Article 1: The literature review presented 257 results. Of these, after analyzing the abstracts, 10 studies were selected for complete review and after this stage three studies wereexcluded. Thus, remaining seven articles that met all the inclusion criteria. It appears that there are few studies of oropharyngeal swallowing in palliative care. Among recent articles on the subject, case studies prevail and papers that address patients with different health involvements, such as dementia, Parkinson's disease, Amyotrophic Lateral Sclerosis and cancer. Article 2: The patients showed equaldistribution between the sexes, mean age of 67, predominating patients with neurological affections, with the highest concentration of the classification in PPS between 20% and exclusive oral feeding. As for the caregivers, the majority were female, with a mean age of 52.6 years. The study prevailed caregivers with low education, member of the patients family, especially son / daughter and spouse. Very few caregivers reported having a formal training course and few mentioned overworkassociated with caregiving activities. Article 3: The majority of caregivers did not refer any questions about the patient's feeding possibilities. Many caregivers believe that patients feel the need to eat, discomfort and difficulties associated with feeding. With regard to the feeding route, the conduct that the caregiver would like to be taken if the patient under his care could eat only in small amounts by mouth was to keep this theexclusive feeding route. In the case of the patient not being able to feed this way, few have chosen to maintain feeding exclusively by oral means. Most could not answer the questions about the action to be taken if the patient is in use of enteral feeding without benefits. Statistically significant associations were found between the expectations of the caregiver about the feeding route and the variables feeding route and disease of the patient. Conclusion: It is believed that the data found in this studymay contribute to the enhancement of caregiver's opinion with regard to the definition of patients feeding route in palliative care. The resulting information from this work, together with the existing literature, will reflect and thus make more appropriate practices, adding quality of care provided to patients in palliative care and their caregivers.